Prevalence and Mophometry of Os Peroneum amongst Central Indians - Pragati S. Mittal; Sharda S. Joshi; Rupa Chhaparwal; Subhash D. Joshi (Journal of Clinical and Diagnostic Research, 2014)
Introduction: Os Peroneum is round or oval shaped sesamoid within the substance of the Peroneus longus tendon as it plays on the Cuboid bone. Materials and Methods: Thirty six embalmed cadavers were dissected bilaterally. Lateral part of foot and sole was dissected to expose Peroneus longus tendon and Os Peroneum. Measurements of Os Peroneum and articular surfaces of cuboid (calcaneum) were taken by the Digital Vernier Caliper. Histological and Radiological Examinations of Os Peroneum were also done. Observation: A flattened oval enlargement i.e. Os Peroneum was found in all the tendons examined. The deep surface of Os Peroneum (i.e. articular surface) was concave, smooth and shiny; sometimes divided into two parts. There was a well defined convex articular facet on the Cuboid at the proximal end of the peroneal sulcus, which sometimes extended proximally on to the Calcaneum forming a synovial joint. Results: Average length of Os Peroneum was found to be 13.35 mm (Right - 13.35 mm, Left - 13.35 mm). Average breadth of Os Peroneum was 8.96 mm (Right - 8.87 mm, Left - 9.05 mm). Average thickness of Os Peroneum was 4.11 mm (Right - 4.13 mm, Left - 4.10 mm). Incidence of double articular facets on cuboid and Calcaneum was more on the right side (25.80%) than the left (16.20%). Conclusion: Findings suggest that Os Peroneum is present at the site of angulations of Peroneus Longus tendon with attendant change in direction and the exposure to various stresses and strains leading to its thickening and formation of Os Peroneum.